The empire of the self : - Star, Christopher. (Johns Hopkins University Press, 2012)
He demonstrates a significant point of contact between two writers generally thought to be antagonists–the idea that imperial speech structures reveal the self.
Bibliographic Level Mode of Issuance: Monograph
Keywords: Seneca; Lucius Annaeus; Petronius Arbiter.; Satyricon.; Politics in literature.; Latin literature